Prevalence and correlations of hepatorenal functions in diabetes and cardiovascular disease among stratified adults - Nwose, Ezekiel Uba; Obianke, Joshua; Richards, Ross Stuart; Bwitit, Phillip Tederera; Igumbor, Eunice Obiajuru (Acta Biomedica Atenei Parmensis, 2019)
Background: The vulnerability of older adults to diabetes and cardiovascular complications is a global concern. Hepatorenal pathophysiology is implicated in these complications, but has yet to be clearly established, especially from rural low-mid income countries. This study investigates differences in prevalence of diabetes in aging groups and correlations of age with hepatorenal variables. Methods: 203 participants of both sexes above the age of 18 years underwent anthropometric measurements at Catholic Hospital, Abbi, Nigeria. Questionnaires collected demographic information and medical history. Urinalysis as well as routine liver and renal function tests were performed. Data analysis included determination of levels of hepatorenal abnormalities and prevalence of diseases in age groups. Percentage of disease subpopulations made up by each age-group was also determined as well as Pearson’s correlation coefficient between age and hepatorenal variables, and comparison of average age and hepatorenal variables in disease subgroups. Results: Percentage hepatorenal abnormalities are not significantly different between age-groups. There is no significant difference in percentage level of disease between groups, but in age-groups constituting disease sub-populations (p<0.00001). The apparently healthy subpopulation comprises of younger adults compared to older adults constituting diabetes and hypertension (p < 0…). Age shows moderate correlation with renal function parameters, especially urea and chloride (r = 0.42), but relatively insignificant with liver function variables. Conclusion: This report affirms that diabetes cardiovascular co-morbidity comes with aging. It also indicates that renal pathophysiology may be more associated, than liver, functions in the vulnerability of adults.